Small manufacturing business in Northern Ireland - Bates, James; Bell, Maeve (Statistical and Social Inquiry Society of Ireland, 1973)
Small businesses play a vital role in the economy of Northern Ireland. In manufacturing industry 1,252 out of a total of 1,542 establishments employ fewer than 100 people. The Bolton Committee commissioned a great deal of valuable research into the problems of small businesses in Great Britain, but these researches did not extend to Northern Ireland. In order to make a start in filling in some of the gaps the authors designed a pilot survey to collect and analyse information on some of the operations of a number of small manufacturing businesses, to find out what the owners and managers regarded as their chief difficulties and problems. The main problem areas about which information was sought were management, finance, marketing, labour relations, training, and the use of advisory services.
Read before the Society, 30 April 1973
Keywords: Small manufacturing firms; Northern Ireland industry; Firm size; Industrial organisation; 314.15